Supercritical fluids and phase behavior in heterogeneous gas-liquid catalytic reactions - Pereda, Selva (2005)
Gas-liquid catalyzed reactions carried out in a supercritical medium take advantage of the high reaction rates and improved selectivities that can be achieved by having reactants and products in a homogeneous phase. In this work, the phase behavior of several supercritical reactions are analyzed and the selection of adequate solvents is discussed. The reactions studied include the hydrogenation of terpenic compounds and unsaturated aldehydes, and the hydroformylation of hydrocarbons to produce aldehydes. Recent experimental results from the literature on the kinetics and selectivities of these reactions are discussed on the basis of the phase equilibrium scenario under the reaction conditions.